Ulnar Neck Fractures Associated with Distal Radius Fractures - Özkan, Sezai; Fischerauer, Stefan F.; Kootstra, Thomas J.M.; Claessen, Femke M.A.P.; Ring, David (Journal of Wrist Surgery, 2018)
Background There is little published data to guide management of ulnar neck fractures associated with fractures of the distal radius.Purpose As unplanned surgery usually reflects adverse events and this injury combination is relatively uncommon, we used a large database to study the incidence of unplanned surgeries after surgical and nonsurgical treatment of distal metaphyseal ulna fractures associated with a distal radius fracture and identify factors associated with these unplanned surgeries.Patients and Methods We identified 277 patients with an ulnar neck fracture associated with a distal radius fracture. Fifty-six (20%) ulnar neck fractures were initially treated operatively and six of them (11%) had a second, unplanned surgery. Of the 221 initially nonoperatively treated fractures, only one (0.45%) had a subsequent unplanned surgery that seemed unrelated to the fracture (ulnar nerve neurolysis).Results Bivariate analysis showed that younger age, open fracture, multifragmentary fractures, and initial operative treatment of the ulnar neck fracture were significantly associated with unplanned surgery. A multivariable analysis was not feasible due to the small number of unplanned surgeries.Conclusion Eighty percent of ulnar neck fractures associated with a fracture of the distal radius was treated nonoperatively in our region, and subsequent surgery for problems was very uncommon. Operative treatment and fracture complexity were associated with unplanned surgery, which reflected some measure of injury severity, technical inadequacy, and inherent problems associated with surgery.Level of Evidence Level II, prognostic study.
Keywords: ulnar neck fractures; distal radius fractures; adverse events; unplanned surgery